Cardiovascular Outcomes, Hospitalization, and Mortality following Amiodarone-Induced Thyrotoxicosis - Irene Serrano; Pedro Iglesias; Juan J. Díez (Experimental and Clinical Endocrinology & Diabetes, 2026)
Abstract Amiodarone-induced thyrotoxicosis is a recognized adverse effect of amiodarone therapy. However, its long-term effects on cardiovascular morbidity, hospitalization, and mortality remain insufficiently characterized. The objective of this study is to evaluate the incidence of cardiovascular events, hospitalizations, and all-cause mortality following amiodarone-induced thyrotoxicosis and to assess their association with clinical, biochemical, and therapeutic parameters. A retrospective cohort study was conducted including 113 adult patients diagnosed with amiodarone-induced thyrotoxicosis and followed at a tertiary endocrinology center between 2008 and 2024. Clinical and biochemical characteristics, therapeutic interventions, cardiovascular events, hospital admissions, and mortality were recorded. The event-free survival was evaluated using Kaplan–Meier curves, and predictors of outcomes were assessed using Cox proportional hazard regression models. Fifty patients (44.2%) were classified as amiodarone-induced thyrotoxicosis type 1 and 63 patients (55.8%) as amiodarone-induced thyrotoxicosis type 2. Over a median follow-up of 52 months, 42.5% experienced at least one cardiovascular event, 38.0% required hospitalization, and 33.6% died. Serum free thyroxine levels at diagnosis were significantly higher in patients who developed cardiovascular events (hazard ratio: 2.6; 95% confidence interval: 1.9–3.7 vs. hazard ratio: 2.3; 95% confidence interval: 1.6–3.4 ng/dL; p=0.042). Kaplan–Meier analysis showed reduced survival in older patients (p